Uji Aktivitas Antioksidan Kombinasi Ekstrak Tanaman Daun Alpukat (Persea Americana Miller) Dan Daun Pucuk Merah (Syzygium Myrtifolium Walp) Dan Penetapan Kadar Flavonoid Total Ekstrak Tunggal - Mei Adelia Sabrina; Nuraini Harmastuti; Ghani Nurfana Fadma Sari (Jurnal Farmasi Indonesia, 2025)
Antioxidants are compounds that can counteract free radicals. This study aims to test the antioxidant activity of avocado (Persea americana Mill.) and red shoot (Syzygium myrtifolium Walp.) leaf extracts, determine total flavonoid levels and compare with quercetin compounds. Extraction with 96% ethanol using maceration method. DPPH free radical activity test of avocado leaf and red shoot extract combination variation (1:3, 2:2, and 3:1) using UV-Vis spectrophotometry. The results of analysis were tested statistically using SPSS. Antioxidants are compounds that can counteract free radicals. The results of total flavonoid content of avocado leaf extract and red shoots are 45,20 and 14.46 mgQE/g. Combination of avocado leaf and red shoot extracts has strong antioxidant activity. The 3:1 ratio of extracts showed the highest antioxidant activity.